APLIKASI ATMEGA8535 SEBAGAI PENGONTROL ALAT PENETAS TELUR - Achmad Rofingi; Bambang Supradono; Achmad Solichan (PSTE UNIMUS, 2011)
Poultry demand increasingly higher demands adequate supply of poultry meat in the community. Utilizing modern farming technology for the mass production of seedlings poultry egg incubator that uses electrical equipment. The tool have a manual thermostat can not adjust the type of eggs that will be hatched and can not compensate for extreme weather changes. Microcontroller technology produces devices that can regulate the temperature of the egg incubator and compensate for extreme climate change. In this research aims to apply egg incubator tool microcontroller ATMega8535 as a temperature regulator.Keywords: egg incubator equipment, temperature control, ATMega8535